Risk Factors For Hyperuricemia In Chinese Centenarians And Near-Centenarians - Han QX; Zhang D; Zhao YL; Liu L; Li J; Zhang F; Luan FX; Liu DW; Liu ZS; Cai GY; Chen XM; Zhu HY (Clinical Interventions in Aging, 2019)
Qiu-Xia Han,1–3,* Dong Zhang,1,* Ya-Li Zhao,4 Liang Liu,5 Jing Li,5 Fu Zhang,5 Fu-Xin Luan,5 Dong-Wei Liu,3 Zhang-Suo Liu,3 Guang-Yan Cai,1,2 Xiang-Mei Chen,1,2 Han-Yu Zhu1 1Department of Nephrology, Chinese PLA General Hospital, Chinese PLA Institute of Nephrology, State Key Laboratory of Kidney Diseases, National Clinical Research Center for Kidney Diseases，Beijing Key Laboratory of Kidney Diseases, Beijing 100853, People’s Republic of China; 2Medical College, Nankai University, Tianjin 300000, People’s Republic of China; 3Department of Nephrology, The First Affiliated Hospital of Zhengzhou University, Research Institute of Nephrology of Zhengzhou University, Key Laboratory of Precision Diagnosis and Treatment for Chronic Kidney Disease in Henan Province, Zhengzhou 450052, People’s Republic of China; 4Central Laboratory, Hainan Branch of Chinese PLA General Hospital, Sanya 572000, People’s Republic of China; 5Management Department, Hainan Branch of Chinese PLA General Hospital, Sanya 572000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Han-Yu Zhu; Xiang-Mei ChenDepartment of Nephrology, Chinese PLA General Hospital, Chinese PLA Institute of Nephrology, State Key Laboratory of Kidney Diseases, National Clinical Research Center for Kidney Diseases, Beijing Key Laboratory of Kidney Diseases, 28 Fuxing Road, Haidian District, Beijing 100853, People’s Republic of ChinaTel +86 10 6693 7763; +86 10 6693 7748Email hanyuzhu301@126.com; xiangmeichen301@126.comPurpose: Hyperuricemia is an important potential pathogenic factor for hypertension, cardiovascular disease and stroke. The current study aimed to investigate the prevalence of hyperuricemia and its relationship to lifestyle characteristics and dietary habits in centenarians and near-centenarians.Patients and methods: In total, 966 centenarians and 788 near-centenarians were included. Community-based surveys were conducted to collect information about lifestyle. Blood examinations were performed using enzymatic assays. T-tests and χ2 tests were used to investigate significant indicators of hyperuricemia, and multivariate logistic regression was used to analyze the related risk factors. A comprehensive analysis of nineteen modifiable factors, including lifestyle characteristics, dietary habits, general characteristics and blood test indexes, was conducted.Results: The prevalence of hyperuricemia was 29.02%. The percentage of men, waist circumference (WC), waist-hip ratio, estimated glomerular filtration rate (eGFR), levels of total protein (TP), alanine aminotransferase, aspartate aminotransferase, triglycerides, high-density lipoprotein cholesterol, serum homocysteine, serum uric acid, serum urea and serum creatinine, passive smoking, alcohol consumption, snoring, preference for fried flavors, and meat, seafood and vegetable consumption were significantly different between the hyperuricemia group and the normouricemia group (p<0.05). Multivariate logistic regression analysis showed that WC (OR=1.020), eGFR (OR=0.960), TP level (OR=1.038), serum urea level (OR=1.154), passive smoking (OR=2.589), snoring (OR=2.003), meat consumption (OR=2.506), seafood consumption (OR=1.422) and vegetable consumption (OR=0.521) were significantly associated with the risk of hyperuricemia (p<0.05).Conclusion: Low eGFR and vegetable consumption, high WC, TP, and serum urea levels, passive smoking, snoring, and high meat and seafood consumption were independent risk factors for hyperuricemia. It is recommended that people at high risk for hyperuricemia should actively limit their intake of fried food, alcohol and purine-rich food, increase their intake of fresh vegetables, actively treat sleep apnea syndrome, avoid passive smoking, maintain a healthy WC and seek to improve their kidney and liver function.Keywords: centenarians, hyperuricemia, lifestyle, dietary, risk factors